Tahqiq wa dirasat Kitab raf' al-hijab'an tanbih al-kuttab lil-Imam al-Rua'yni - al-Zahrani, Saeed Mohsen Saleem (2016)
Commentary on a poem by Muhammad ibn Jabir, dealing with the difference between the letters za and dad.
Cd yang di sertakan duplikasi kepada tesis bercetak dan tidak boleh dirujuk / dipinjam.
Tesis (Ph.D) - Universiti Kebangsaan Malaysia, 2016.
Rujukan : mukasurat 220-237.
Keywords: al-Ruayni, Ahmad ibn Yusuf, -- -1378 -- Criticism and interpretation; Ibn Jabir, Muhammad ibn Ahmad, -- 1298 or 1299-1378 or 1379. -- Criticism and interpretation; Universiti Kebangsaan Malaysia -- Dissertations; Dissertations, Academic -- Malaysia; Arabic language -- Grammar -- Poetry -- Early works to 1800.; Arabic language -- Grammar -- Manuscripts